Tiada Sesuatu Perbuatan Boleh Dijatuhi Pidana Melainkan Lewat Kekuatan Ketentuan Perundang-Undangan - Amstrong Harefa; Jesslyn Elisandra Harefa (Pusat Riset dan Inovasi Nasional, 2025)
The principle of legality is a legal principle that states that every act may only be subject to sanctions if it has been stipulated in the legislation before the criminal act is committed. The research aims to analyze the necessity of a law before a criminal event occurs; analyze the assessment of an act that is not analogous; analyze the need for the principle of legality to protect individuals from arbitrary actions by judicial officers. The research method is the normative legal method, by adopting conventions, legislation, law books, journals, articles, the internet. Furthermore, comprehensively reviewing the literature so that maximum results are obtained. The results of the research, law enforcement that is fair, pure and consistent is still difficult to achieve considering that many officers still do not fully understand the meaning of the principle of legality so that they often make mistakes in considering imposing criminal sanctions, and often their decisions exceed their authority. Human rights are inherent rights in individuals, so individuals should get their rights. Protection of individual rights is mandated in the 1945 Constitution Article 28G paragraph (1) Article 28H paragraph (1). Legal certainty is a vital element in building an honest and fair legal strategy. It is expected that when laws are created, they should be in accordance with a systematic, democratic mechanism based on empirical observation results, so that errors in the application of the law can be minimized. Thus, all people get legal certainty where their rights are protected and maintained, on the other hand, each individual is aware not to do prohibited acts because every action has logical and firm consequences.